A spatial decision support system for educational planning identifying areas of excellence using UPCAT data - Figueroa, Ligaya Leah Lara (2007)
This paper documents the components, potentials, and results of using a spatial decision support system (SDSS). It focuses on the relevance of using this system to aid educational planning in the Philippines. The system is built using ESRIs ArcMap. Data used and manipulated in the system involves: UPCAT scores, test center locations, secondary school locations, secondary school populations, and Philippine geographical data. Through density maps, colored maps, lists, and graphs, the system can show areas with the highest and lowest scores, the most and the least applicants, yearly trends and school details. These visual representations may be used with road networks, test center locations, and other geographical data available as background. Using these tools, illustrations and comparisons can be made by the analyst per municipality, province, and region. Suggestions and visual representations regarding performance and excellence in secondary education are given for selected schools, municipalities, provinces, and regions in this paper. As an example of the use of the SDSS, a hypothesis that students near coastal areas have better academic performance is tested. Since most of the data are associated with the UPCAT, the system may be used for UPCAT-related strategies and decisions. UPCAT test center locations are evaluated using applicant population, road networks, and land contour maps.